Grass Carp Reovirus VP35 Degrades MAVS Through the Autophagy Pathway to Inhibit Fish Interferon Production - Lu, Long-Feng; Zhang, Can; Li, Zhuo-Cong; Zhou, Xiao-Yu; Jiang, Jing-Yu; Chen, Dandan; Zhang, Yong-An; Li, Shun (Frontiers in Immunology, 2021)
Fish interferon (IFN) is a crucial cytokine for host to resist external pathogens, conferring cells antiviral capacity. Meanwhile, grass carp reovirus (GCRV) is a strong pathogen that causes high mortality in grass carp. Therefore, it is necessary to study the strategy used by GCRV to evade the cellular IFN response. In this study, we found that GCRV VP35 inhibits host IFN production by degrading mitochondrial antiviral signal protein (MAVS) through the autophagy pathway. First, overexpression of VP35 inhibited IFN activation induced by polyinosinic-polycytidylic acid (poly I:C) and MAVS, and the expression of downstream IFN-stimulated genes (ISGs) was also decreased by VP35 under stimulation. Secondly, VP35 interacted with MAVS; the experiments of truncated mutants of MAVS demonstrated that the caspase recruitment domain (CARD) and proline-rich (PRO) domains of MAVS are not necessary for this binding. Then, MAVS was degraded by VP35 in a dose-dependent manner, and 3-MA (the autophagy pathway inhibitor) significantly blocked the degradation, meaning that MAVS was degraded by VP35 in the autophagy pathway. The result of MAVS degradation suggests that the antiviral capacity of MAVS is depressed remarkably when interrupted by VP35. Finally, for host cells, VP35 reduced ifn transcription and made cells vulnerable to virus infection. In conclusion, our results reveal that GCRV VP35 impairs the host IFN response by degrading MAVS through the autophagy pathway, supplying evidence of a fish virus immune evasion strategy.